Novel process for the synthesis of class I antiarrhythmic agent (+/-)-cibenzoline and its analogs - Gholap, Atul R.; Paul, Vincent; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Synthesis of (+/-)-cibenzoline and its analogs has been achieved by a simple sequence of reactions. The diaryl cyanoolefin intermediate 3 could be prepared by Knoevenagel condensation of benzophenone with ethylcyanoacetate to form the tetra-substituted olefin intermediate 2 followed by Krapcho deethoxycarbonylation or from beta-hydroxynitrile intermediate 2' followed by the elimination of hydroxyl group respectively. The 2,2-diphenylcyclopropanecarbonitrile 4 was synthesized from intermediate 3 by cyclopropanation, which was converted to (+/-)-2-(2,2-diphenylcyclopropyl)-2-imidazoline 5 by reaction with ethylenediamine in the presence of a catalytic amount of sulfur. Moreover, the obtained 2-imidazolines were smoothly oxidized to the corresponding imidazoles 6 in good to moderate yields.
Keywords: Benzophenone; cibenzoline; cyclopropanation; diaryl cyanoolefin